Psychological Burden in Female, Iraqi Refugees Who Suffered Extreme Violence by the “Islamic State”: The Perspective of Care Providers - Rometsch-Ogioun El Sount, Caroline; Denkinger, Jana Katharina; Windthorst, Petra; Nikendei, Christoph; Kindermann, David; Renner, Viola; Ringwald, Johanna; Brucker, Sara; Tran, Virginia M.; Zipfel, Stephan; Junne, Florian (Frontiers in Psychiatry, 2018)
Introduction. A large number of refugees suffer from mental disorders such as posttraumatic stress disorder (PTSD). In the context of a special quota project, 1100 Yazidi women from Northern Iraq who had suffered extreme violence by the so-called Islamic State (IS) were brought to Germany to receive specialized treatment. This study aims to investigate the psychological burden and trauma-related symptoms of these female IS-victims from the perspectives of their care providers. Material and methods. Care providers with various professional backgrounds (N = 96) were asked to complete a self-developed questionnaire on a Likert-type scale ranging from 1 (very low) to 7 (very high) analyzing the psychological burden and trauma-related symptoms of the IS-traumatized women since their arrival in Germany. We controlled for potential confounders, namely the care providers’ personal experiences of trauma and flight, by using chi-square tests. Results. The mean psychological burden for the whole period in Germany as perceived by care providers was M = 5.51 (SD = 0.94). As the main factors of distress the care providers reported: worries about family members in Iraq (M = 6.69; SD = 0.69), worries about relatives’ possibilities to be granted asylum in Germany (M = 6.62; SD = 0.68), and uncertainties regarding their future (M = 5.89; SD = 1.02). The most prominent trauma-related psychological symptoms were nightmares (M = 6.43; SD = 0.54). The care providers reported that somatic complaints have been present among the refugees in the following manifestation: pain (M = 6.24; SD = 1.08), gastrointestinal complaints (M = 4.62; SD = 1.62), and dizziness (M = 4.40; SD = 1.59). The care providers’ personal experiences of trauma and flight had no significant influence on their response behavior. Discussion. Care providers working with IS-traumatized female refugees evaluate the psychological burden and trauma-related somatic and psychological symptom loads of their clients as very high. The results of this study provide important information about the perceptions of care providers working in a refugee-services context and may provide insights for the progression of specialized treatment programs and interventions for highly traumatized refugees and culture-sensitive training programs for their care providers.